Gravyland : writing beyond the curriculum in the City of Brotherly Love - Parks, Stephen, 1963- (Book collections on Project MUSE., 2010)
In G ravyland, Parks chronicles the history of an urban university writing program and its attempt to develop politically progressive literacy partnerships with the surrounding community while having to work within and against a traditional educational and cultural landscape. He details the experience of Temple University's New City Writing program from its beginning as a small institute with one program at a local public school to a multifaceted organization, supported by large multiyear grants and establishing partnerships across the diverse neighborhoods of Philadelphia. The author describes classrooms where the community takes a seat and becomes part of the conversation-a conversation that readers of Gravyland share through the inclusion of a selection of passages produced by community writers published by New City Community Press. While Parks celebrates classroom success in generating knowledge through dialogue with the larger community, he also highlights many of the obstacles the organizers of the New City Writing program faced. The author shows that writing alliances between universities and communities are possible, but they must take into account the institutional, economic, and political pressures that accompany such partnerships. Blending the theoretical and practical lessons learned, Parks elucidates New City Writing's effort to offer a new model of education, one in which the voice of the professor must share space with the voices of the community, and one in which students come to understand that the right to sit in a classroom is the result not just of nationalist war but of peaceful civil disobedience, of community struggles to gain self-recognition, and of collective efforts to seek social justice.